2010
DOI: 10.1111/j.1551-2916.2010.04094.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Ferroelectric Lead Zirconate Titanate Thin Films by Microwave Annealing at Low Temperatures

Abstract: Lead zirconate titanate (PZT) thin films were coated on Pt/Ti/SiO2/Si substrates by the sol–gel method and then crystallized by microwave annealing using a single‐mode 2.45 GHz microwave irradiation system in the magnetic field. The crystalline phases and microstructures as well as the ferroelectric properties of the PZT films were investigated as a function of the elevated temperature generated by microwave irradiation, and the phase transition in the crystallization of the PZT thin films was discussed. X‐ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In this study, the PZT films were annealed by microwave irradiation with a fast heating rate of about 60°C/s from room temperature to 550°C, which is fast as that in RTA process. On the other hand, it has been assumed that microwave energy might induce the formation of the perovskite phase in the PZT films by direct microwave irradiation . Many researchers reported that ceramics were densified by microwave heating at lower temperatures and for shorter times than conventional method due to the enhanced diffusion by microwave field .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, the PZT films were annealed by microwave irradiation with a fast heating rate of about 60°C/s from room temperature to 550°C, which is fast as that in RTA process. On the other hand, it has been assumed that microwave energy might induce the formation of the perovskite phase in the PZT films by direct microwave irradiation . Many researchers reported that ceramics were densified by microwave heating at lower temperatures and for shorter times than conventional method due to the enhanced diffusion by microwave field .…”
Section: Resultsmentioning
confidence: 99%
“…The deposition techniques of lead zirconate titanate (Pb(Zr x Ti 1− x )O 3 :PZT) thin films have been widely studied, because of the large number of potential applications of Pb(Zr 0.52 Ti 0.48 ) O 3 (PZT) thin films in nonvolatile ferroelectric random‐access memories and micro‐electromechanical systems (MEMS) such as atomic force microscopy cantilevers and broadband MEMS shunt switches . Recently, microwave heating techniques have attracted considerable attention as a new process for preparation of ferroelectric PZT films because they offer many advantages such as energy saving, fine microstructure, short processing time, and low processing temperature . For example, perovskite PZT films with good electrical properties could be obtained by multimode microwave irradiation with a frequency of 28 GHz at 480°C for only 5 min .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations